The influence of the media on practice in mental health: a bricolage of a single case study. Issue 5 (2nd September 2016) - Wibberley, Christopher; Murphy, Neil
Abstract: This paper has its genesis in the convergence of two individuals' interests – one with a long-standing interest in representations of mental health and one with an interest in the use of bricolage as a research approach. These interests converged around the ways in which mental health care practitioners might react to and subsequently reflect on images of mental health they came across in the media. A bricolage was developed relating to newspaper coverage of a homicide carried out by someone with a mental health problem. The bricolage draws on the assumption that practitioners will have immediate reactions to material they come across, take a more considered overview of this material, and subsequently attempt to contextualize this reflection in terms of academic literature. The bricolage as presented mirrors this process for an experienced practitioner. Suggestions are made concerning the use of newspaper reports on mental health, to enable both novice and experienced practitioners to gain vicarious experience through reflection on these reports.